2015
DOI: 10.5688/ajpe799131
|View full text |Cite
|
Sign up to set email alerts
|

An Industrial Engineering Approach to Cost Containment of Pharmacy Education

Abstract: A 2-semester project explored employing teams of fourth-year industrial engineering students to optimize some of our academic management processes. Results included significant cost savings and increases in efficiency, effectiveness, and student and faculty satisfaction. While we did not adopt all of the students' recommendations, we did learn some important lessons. For example, an initial investment of time in developing a mutually clear understanding of the problems, constraints, and goals maximizes the val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Internal performance should be done by optimization and standardization of processes. The standardizationreducesthe cycle time of processes (Duncan et al, 2015), thereforethe number of times of process's performance would increase perperiod i.e., process frequency would increase. External performance should be done by ensuring successful development process which would perform constantly, ensuringthat the company can keep up with changes in the environment.…”
Section: Background Of Researchmentioning
confidence: 99%
“…Internal performance should be done by optimization and standardization of processes. The standardizationreducesthe cycle time of processes (Duncan et al, 2015), thereforethe number of times of process's performance would increase perperiod i.e., process frequency would increase. External performance should be done by ensuring successful development process which would perform constantly, ensuringthat the company can keep up with changes in the environment.…”
Section: Background Of Researchmentioning
confidence: 99%
“…The result of this study, by improving the management system at university. Namely a significant cost savings of around 60,000 USD per year, increased efficiency, effectiveness and students and faculty satisfaction (Duncan et al, 2015). The results revealed that, using a combination of methods namely ABC analysis of fuzzy weighting and U-control diagrams, was very effective to assist in the assessment system in the quality of learning processes at the university level for the long term (Carlucci, Renna, Izzo, & Schiuma, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Prior studies also suggest that moving pharmacy education (and likewise, other health professions programs) toward a more efficient model, defined as a model in which the financial burden on students is reduced, would require limiting unnecessary costs, identifying areas of overspending, and implementing cost containment strategies. 48,49 In addition to reducing the burden of high tuition, colleges of pharmacy and other health professions have an opportunity to help students learn about finances. 50 By adding a personal finance course or group activities focused around topics in personal financial management, such as budgeting, savings, and managing debt, colleges will help students understand the true cost of taking out loans.…”
Section: Discussionmentioning
confidence: 99%